Experimental analysis of a composite bridge under high-speed train passages. (2017) - Somaschini, Claudio; Matsuoka, Kodai; Collina, Andrea
Abstract: Evaluation of resonances phenomenon in high-speed railway bridges during train passage is a dominant issue in order to confirm the structural safety of the bridge and the stability of the ballast on bridge deck. The Sesia viaduct, located in the Turin-Milan high-speed rail line, is one of the most investigated high-speed railway bridges. The maximum accelerations and the resonance train speed were predicted while the bridge vibration modes and the effect of adjacent spans on these were estimated through some detailed experimental and numerical investigations. Nevertheless, some important points remain unclear, such as the actual resonance speed and the influence of deck local vibrations. To verify and clarify these issues, experimental dynamic analyzes based on acceleration measurements of the Sesia viaduct under ETR1000 train passages with speed up to 374km/h were conducted in this study. In the measurements, accelerometers were installed not only on steel box girder but also on concrete deck slab in order to identify local vibration modes of deck members so as to estimate their effect on the evaluation of the accelerations. Comparing the maximum accelerations up to 15Hz with various train speeds, the resonance speed corresponding to the first bending mode of the Sesia viaduct was identified. Furthermore, an analysis based on the identification of the natural frequencies clarified that the high-order resonances between passing train and deck local vibration modes have the largest impact on the maximum acceleration up to 30Hz which is the limit used for the verification of ballast stability in the Eurocode.